Batchoy restaurants in Iloilo City company profile, marketing mix and consumer preference - Asong, Pearl Novie; Aquino, Lynnie Faith; Bado, Clarissa; Fojas, Julie Anne; Muyana, Erika Marie; Servacio, Karen; Villavicencio, Angelica
This research determines the company profile (mission statement, company objectives and business portfolio), marketing mix (product, price, place and promotion), and consumer preference (consumer buying behavior and consumer demand) of Batchoy restaurants in Iloilo City. The Batchoy restaurants included in the study sre Ted's Old Timer Lapaz Batchoy, Deco's Original Lapaz Batchoy and Netong's Original Special Lapaz Batchoy. The local of the study is the City of Iloilo, where forty-three (43) customers and two (2) managers are selected based on a convenient sampling. Findings show that company profile greatly varies from one restaurant to another. Findings include the socio-demographic of respondents vary with age of customers ranging from 18 to 29 years old, mostly single; more women than men and most customers have an income level of less than Php 10,000. Also, most of them have attained a college education, either college graduates or have at least some years in college. For the marketing mix, in terms of product, most of the excellent ratings were taken by Deco's. Netongs has the most authentic price but the least affordable. As to lighting and layout, Netong's leads the standing among the three competing restaurants. Moreover, Netong's got the highest ranking in promotion which means it is the most recognized Batchoy establishment, followed by Deco's and Ted's. For the consumer preference, most customers eat Batchoy once or twice a month and Deco's is the most preferred restaurant. When dining in, most customers still look for the taste of the original Ilonggo dish and Puto is the most preferred side dish. The results show that Batchoy restaurants must have their mission statement, company objectives and business portfolio ready for its customers. They should also have adequate amount of knowledge regarding customer feedback on their marketing mix and consumer preferences to deliver the quality and services needed by Batchoy diners.